A Fapemig e a produção científica mineira de 2007 a 2016 - Cury Junior, Célio Hely (2018)
We live with new necessities of research and consequently with new political forms and arrangements of research, demanding a new look on and for them. This is a study of FAPEMIG and the promotion of scientific research. Having as thesis, if FAPEMIG predominantly serves the reproductive interests of capital, has as main objective, understand and analyze the directions of FAPEMIG proposals in the last decade, thus, identifying if the agency complies with neoliberal international scientific guidelines, promoting higher investments in knowledge areas that respond to the productive interests of capital. More specifically, present FAPEMIG and its budget distribution for the different sets of promotion modalities; understand how it has been building the system of promotion for Universal Demand and Induced Demand projects launched by the agency between the years of 2007 to 2016 and if these, articulating through demands of the capitalist way of growth and economic-social development, imply in higher or lower investments for certain knowledge areas (humanities areas, for example) and even for certain research institutions in Minas Gerais; and finally, understand the world of work transformations by configuring the process and organization of academic and technological research in Brazil, in the neoliberalism context. Taking as a reference the dialectic analytics perspectives manifested in the principle of totality which the particular is explained in general and vice versa, an investigation was carried out having as reference the FAPEMIG action from the possible influences received in an international scope. In this sense, a bibliographical survey and documentary analysis was carried out expressed in the research notices, Activity Reports and Deliberations of the Curator Council. However, FAPEMIG has a strong and competent system of research promotion, focused on human resources formation, basic research and applied research, and seeks to use standards and criteria to research promotion, as close as possible to those internationally consolidated, coupled and defined by some policy requirements under capital domain. In this perspective, the investments presented by FAPEMIG are indispensable to the induction and promotion of research and scientific and technological innovation in the State of Minas Gerais. That way, FAPEMIG, as the largest research promotion agency in Minas Gerais and the second largest in Brazil, has established, through a solid ST&I system, the research, programs and projects development is associated with great social and economic problems of the State, taking into account the reproductive interests of capital. This sense of giving utility to research has reoriented researches and universities to adapt their research practices to neoliberal objectives.